Pergeseran Fungsi dan Bentuk Ronggeng di Jawa Barat - Sujana, Anis (PANGGUNG, 2012)
Generally the term ronggeng is used to call female performer, Ã¢â¬Ëbeing paidÃ¢â¬â¢, and is usually i- maged badly. However, in the other side, ronggeng also performs in fecundity rituals and becomes the source of blessing. It can be seen here that ronggeng has double function and role.This writing is aimed at seeking for functions and types of ronggeng arts in western Java. The result shows that in many cases socio-culturally ronggeng is on profane functions, that is, as enter- tainers. Related to their performance techniques, there are several functions: 1) as audience partners in social intercourse dance; 2) as actors in some traditional theatres; 3) as dance performers andÃ¢â¬ËsingleÃ¢â¬â¢ singer as well as jester; 3) as song performers (sinden) in wooden puppet; 5) as performers in magic performance; and 6) as performers in helaran performance. On the other side, ronggeng also has sacred function, that is as the rites performers, especially on fecundity ones; in this case, ronggeng has ambiguous functions, that is as rites performers in one side, and on the other side as entertainers.ÃÂ Keywords: ronggeng, function and type, entertainment, rites.